APELIN-13 LEVEL, DIASTOLIC DYSFUNCTION, AND CARDIAC REMODELING IN PATIENTS WITH ARTERIAL HYPERTENSION AND EXTRASYSTOLE - Ivankova, A.V.; Kuzminova, N.V.; Lozinsky, S.E.; Knyazkova, I.I.; Kulchytska, O.M.; Poberezhets, O.L.; Romanova, V.O. (World of Medicine and Biology, 2024)
A total of 156 patients with stage II hypertension were examined, of whom 124 had frequent extrasystoles and 32 did not have any heart rhythm disorders. All patients included in the study underwent a complete clinical, laboratory, and instrumental examination, including measurement of serum apelin- 13, determination of diastolic dysfunction, and type of structural and geometric cardiac remodeling. The presence of frequent extrasystoles (both supraventricular and ventricular origin) in patients with stage II hypertension was associated with the presence of diastolic dysfunction, namely, with a deterioration in myocardial relaxation capacity. A significant inverse relationship between the level of serum apelin-13 and the presence of frequent extrasystoles, in particular of ventricular origin, male gender, smoking, and hereditary burden in patients with hypertension was established.